Vaccine for streptococcosis - Mohd. Yusoff, Md. Sabri; Mansor, Nur Nazifah (2013)
The present invention relates to a vaccine for treating streptococcosis disease that occurs in fish. The vaccine comprises of a recombinant microorganism expressing an antigenic protein of Streptococcus agalactiae, wherein the antigenic protein is cell wall surface anchor family protein. The vaccine is administered orally and gives longer period of protection against the disease. The present invention also relates to a method for producing the vaccine.